2020
DOI: 10.1080/21691401.2020.1716780
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine protects PC12 cells from oxidative damage through regulation of miR-199a/HIF-1α

Abstract: Background: Although dexmedetomidine (Dex) has a significant neuroprotective effect in various nerve-damage models, the exact mechanism of which Dex protects cells from oxidative damage is not fully clear. This article recommended the protective effect of Dex on oxidative damage in PC12 cells. Methods: The PC12 cells were incubated by hydrogen peroxide (H 2 O 2) for 24 h and pre-treated by Dex for 30 min. Cell viability, apoptosis, HIF-1a expression and ROS level were detected by CCK-8, apoptosis assay, Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Wu et al confirmed that miR-49 inhibits angiogenesis in breast cancer by targeting HIF-1α (40). Previous studies confirmed that miR-199a protects PC12 cells from oxidative damage by regulating HIF-1α (17). In this study, it was found that downregulation of miR-199a expression could upregulate the expression of HIF-1α, and DMED could upregulate the expression of HIF-1α.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Wu et al confirmed that miR-49 inhibits angiogenesis in breast cancer by targeting HIF-1α (40). Previous studies confirmed that miR-199a protects PC12 cells from oxidative damage by regulating HIF-1α (17). In this study, it was found that downregulation of miR-199a expression could upregulate the expression of HIF-1α, and DMED could upregulate the expression of HIF-1α.…”
Section: Discussionsupporting
confidence: 61%
“…Also, MiR-199a has been shown to inhibit the activity of breast cancer cells (16). Wu et al have confirmed that DMED prevents oxidative damage to PC12 cells by regulating miR-199a/HIF-1α (17). At the same time, DMED attenuates neuronal injury induced by cerebral ischemia-reperfusion (IR) by regulating miR-199a (18).…”
Section: Introductionmentioning
confidence: 99%
“…The present study found that DEX decreased mNSS and improved pathological damage of the cerebral cortex. A previous study also found that DEX protects PC12 cells from oxidative damage via regulation of miR-199a/hypoxia inducible factor 1α (36). Thus, the present study aimed to investigate the association between DEX and miR-199a in neuron injury.…”
Section: Discussionmentioning
confidence: 88%
“…The miR-199 regulates cell proliferation, apoptosis, and ROS production by affecting the Wnt/b-catenin, PI3K/AKT/mTOR, and HIF-1α signalling pathways. In PC 12 cells with H 2 O 2 -induced oxidative injury, dexmedetomidine reduced ROS formation and apoptosis by regulating miR-199a/HIF-1 and simulating PI3K/AKT/mTOR and Wnt/b-catenin signalling pathways (Wu et al, 2020).…”
Section: Neuroprotective Effect Of Dexmedetomidine In Substance-induced Neuronal Injurymentioning
confidence: 93%